1984
DOI: 10.1083/jcb.99.2.615
|View full text |Cite
|
Sign up to set email alerts
|

Components of Torpedo electric organ and muscle that cause aggregation of acetylcholine receptors on cultured muscle cells.

Abstract: The synaptic portion of a muscle fiber's basal lamina sheath has molecules tightly bound to it that cause aggregation of acetylcholine receptors (AChRs) on regenerating myofibers . Since basal lamina and other extracellular matrix constituents are insoluble in isotonic saline and detergent solutions, insoluble detergent-extracted fractions of tissues receiving cholinergic input may provide an enriched source of the AChR-aggregating molecules for detailed characterization . Here we demonstrate that such an inso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
196
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(209 citation statements)
references
References 48 publications
(73 reference statements)
12
196
1
Order By: Relevance
“…One synaptic molecule implicated in the activation of a tyrosine kinase pathway is agrin. This nerve-derived protein originally was isolated for its striking ability to cause AChR aggregation in chick myotubes (Godfrey et al, 1984). The observation that agrin induces tyrosine phosphorylation of the ␤ (Wallace et al, 1991;Qu and Huganir, 1994;Wallace, 1994;Ferns et al, 1996), and perhaps the ␦ (Qu and Huganir, 1994), subunit of the AChR has led to the hypothesis that this is a critical, and perhaps a prerequisite, step in the AChR clustering pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One synaptic molecule implicated in the activation of a tyrosine kinase pathway is agrin. This nerve-derived protein originally was isolated for its striking ability to cause AChR aggregation in chick myotubes (Godfrey et al, 1984). The observation that agrin induces tyrosine phosphorylation of the ␤ (Wallace et al, 1991;Qu and Huganir, 1994;Wallace, 1994;Ferns et al, 1996), and perhaps the ␦ (Qu and Huganir, 1994), subunit of the AChR has led to the hypothesis that this is a critical, and perhaps a prerequisite, step in the AChR clustering pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Postsynaptic membranes of this tissue have provided a rich source for the identification and characterization of many synaptic proteins, including rapsyn, syntrophin, and agrin (Sobel et al, 1977;Godfrey et al, 1984;Froehner et al, 1987). To identify potential binding partners for Grb2 in Torpedo postsynaptic membranes, we used a protein overlay assay in which GST fusion proteins were used to probe membrane proteins separated by SDS-PAGE and transferred to nitrocellulose.…”
Section: Grb2 Fusion Proteins Bind To the ␦ Subunit Of The Achrmentioning
confidence: 99%
“…The chimeric constructs were transfected into COS-7 cells, and the conditioned medium was tested after 2 days for its ability to induce AChR aggregation on cultured chick myotubes under the standard conditions for assaying agrin's activity (Godfrey et al, 1984;Wall ace, 1986). The exchange of the Kpnl fragment (Figure 1) between CBA-1 and ARP-2 cDNA , the shorter of the two agrin-related cDNAs, resulted in two chimeric DNAs_ One having the same 5' end as CBA-1 but lacking regions A and B encoded an CBA-1…”
Section: Expression Of Chimerasmentioning
confidence: 99%
“…Transfection experiments revealed that the proteins encoded by these cDNAs are recognized by anti-agrin antibodies, but unlike agrin, they are inactive in standard AChR aggregation assays. Because the discovery of agrin was based on its ability to cause AChRs to aggregate in cultured chick myotubes (Godfrey et al, 1984;Nitkin et al, 1987) and because the two proteins we describe here lack the AChR aggregating activity, but are highly similarto agrin in structure, we refer to them simply as agrin-related proteins 1 and 2 (ARP-1 and ARP-2). The predicted amino acid sequences of the agrin-related proteins are identical to that of agrin except for the absence of a stretch of 11 amino acids in ARP-1 and stretch es of the 11 and 4 amino acids in ARP-2.…”
Section: Introductionmentioning
confidence: 99%
“…The active protein in the medium conditioned by COS-7 cells transfected with CBA-1 induced the formation of AChR aggregates in a dose-dependent way, as does T. californica agrin (Godfrey et al, 1984). Moreover, the maximal number of aggregates induced by conditioned medium was not increased by the simultaneous addition of T. californica agrin to myotube cultures, indicating that the secreted protein ac ted by the same mechanisms as those used by agrin (conditioned medium, 16.3 ± 0.7 AChR aggregates per myotube segment; conditioned medium + 2 U ofT.…”
Section: Cloning and Functional Expression Of Cba-lmentioning
confidence: 99%